Parameters of Memory Reconsolidation: Learning Mode Influences Likelihood of Memory Modification - Simon, Katharine C.; Nadel, Lynn; Gómez, Rebecca L. (Frontiers in Behavioral Neuroscience, 2020)
When previously consolidated hippocampally-dependent memory traces are reactivated they enter a vulnerable state in which they can be altered with new information, after which they must be re-consolidated in order to restabilize the trace. The existing body of literature on episodic reconsolidation largely focuses on the when and how of successful memory reactivation. What remains poorly understood is how the nature of newly-presented information affects the likelihood of a vulnerable episodic memory being altered. We used our episodic memory reconsolidation paradigm to investigate if the intention to encode impacts what subsequently becomes attributed to an older, reactivated memory. Participants learned two lists of objects separated by 48 hours. We integrated a modified item-list directed-forgetting paradigm into the encoding of the second object list by cueing participants to learn some of the objects intentionally (intentional learning), while other objects were presented without a cue (incidental learning). Under conditions of memory reactivation, subjects showed equal rates of memory modification for intentionally- and incidentally-learned objects. However, in the absence of reactivation we observed high misattribution rates of incidentally-learned objects. We consider two interpretations of these data, with contrasting implications for understanding the conditions that influence memory malleability, and suggest further work that should help decide between them.